The Impact of Raising Awareness of the Speech Act On Speaking Ability across Gender and Proficiency Level - Kobra Ghayebi; Parisa Farrokh (Asociación Colombiana de Profesores de Ingles, 2020)
The present study intended to investigate the possible effects of speech acts strategies on Iranian beginner and intermediate EFL learners' speaking ability. The first step in conducting this research was the administration of QPT as the homogenizing tool. It was administered to 180 beginners and intermediate EFL learners. After analyzing the results, 80 males and females as starters and 80 males and females as intermediate subjects were chosen. Then, the beginner and intermediate EFL learners were randomly divided into control and experimental groups (including 40 beginner male and 40 female EFL learners in each class). Next, a pretest of speaking was administered to all the participants and the experimental groups received speech act role play as treatment. However, the researcher did not use any treatment of speech acts in control groups. After ten sessions, the posttest was administered to all participants. The findings suggested that awareness raising on speech acts resulted in a better speaking ability as compared to the simply traditional teaching of speaking for Iranian intermediate and beginner EFL learners. Additionally, intermediate EFL learners' achievement in speaking was not in line with the beginner EFL learners' achievement in the corresponding group. Finally, it was found that gender does not interact with awareness raising on speech acts in such a way as to produce a statistically significant effect on the beginner and intermediate EFL learners' speaking ability.